First report and molecular characterisation of an adult liver fluke ( Fasciola hepatica) in a brown bear ( Ursus arctos) in Türkiye - Kilinc, Seyma Gunyakti; Kesik, Harun Kaya; Celik, Figen; Simsek, Sami (Elsevier, 2024)
Fascioliasis, caused by the parasite Fasciola hepatica, is a worldwide zoonotic disease that can have serious consequences for livestock, certain wild animals and humans. This study was conducted to morphologically and molecularly characterise a F. hepatica isolate from a brown bear. After examination of the internal organs, a Fasciola sp. isolate was obtained from the bile ducts of the liver. The adult parasite was morphologically analysed under a stereomicroscope and identified as F. hepatica. Measurements of body length, body width and ventral sucker area were then recorded. After isolation of the genomic DNA, a partial gene of the mitochondrial cytochrome oxidase subunit 1 (mt-CO1) was amplified by PCR. The amplified mt-CO1 PCR products were sequenced by one-way sequence analysis. According to the BLAST search results, the sequence of the isolate was identified as F. hepatica. In conclusion, this is the first report on the occurrence of F. hepatica in brown bears and the molecular characterisation of the isolate.
Keywords: Brown bear; Fasciola hepatica; Morphometry; PCR